Bamboo shoot resources of the Philippines II. Proximate analysis, cyanide content, shoot characteristics and sensory evaluation of local bamboo species - Lit, Merdelyn T. (The Philippine Journal of Crop Science, 2010)
Studies on bamboo shoot characteristics and sensory evaluation of several local bamboo species grown in study sites in Laguna and Davao City were conducted. Results of the proximate analysis of fresh and cooked bamboo shoots of Bambusa blumeana (Kauayan-tinik), B. Philippinensis (Laak) and Gigantochloa after (Kayali) showed varying chemical properties. Based from the analysis, B. blumeana and G. after were promising varieties which can be a good source of nutrient-rich vegetable shoots. Cyanide content of fresh shoots of the three-year old clumps in Sta. Cruz Laguna showed that B. Philippinensis contained the highest amount (64.88 ppm) while Gigantochloa after had the lowest content (40 ppm). For the 10-year old clumps from Davao, results showed that fresh shoots of B. vulgaris var. Vulgaris had the highest cyanide content (77.84 ppm) while Dendrocalamus latiflorus had also the lowest (54.21 ppm). Generally, cyanide contents of fresh shoots were significantly higher compared to cooked shoots. Boiling for 15 min had greatly reduced the cyanide content by 75-98% . Based on the pooled means from the two sites, cyanide contents of species belonging to the genus Bambusa were generally higher than those of Dendrocalamus and Gigantochloa. Shoot characteristics among the bamboo species were also significantly different. Sensory evaluation of the shoots of selected bamboo species showed that there were no significant differences in terms of aroma, after-taste, flavor and texture and only significantly different in the color of the shoots. Bamboo shoot preference and acceptability by selected respondents were ranked in descending order. B. blumeana > G. levis > G. after > B. philippinensis. The above results in bamboo shoot plantation establishment, production and processing.